PENGGUNAAN WEBSITE KEMENDAGRI.GO.ID SEBAGAI BENTUK PENINGKATAN KUALITAS LAYANAN PUBLIK - Muh. Rivandy Setiawan (Post Graduate School of Government Science, 2024)
Electronic government is an organization for governments in a country that wants to realize sustainable development for government systems. E-Government is the expected output or result of the goal of developing facilities and infrastructure and providing maximum services to the community. The aim of this research is to find out how the Ministry of Home Affairs website is used as a form of quality public service to the community. This research uses a descriptive qualitative approach. Research with a qualitative descriptive approach is a research method that uses data that is measured qualitatively and the research results are explained using descriptions of words in a narrative. The results of this research result in the conclusion that the Ministry of Home Affairs is trying to improve the quality of public services through the use of the website at https://www.kemendagri.go.id/. The efforts made by the Ministry of Home Affairs to optimize the quality of the public services they provide through the website are by making it easier for the public to access the Ministry of Home Affairs website; provide many menus and features that are very useful for ordinary people in obtaining data or information within the Ministry of Home Affairs; and data that is continuously updated by the public so that they get the latest data and information directly from the Ministry of Home Affairs.